Adaptive block tree structure for video coding - Baek, Aram; Gwon, Daehyeok; Son, Sohee; Lee, Jinho; Kang, Jung‐Won; Kim, Hui Yong; Choi, Haechul (ETRI journal, 2021)
The Joint Video Exploration Team (JVET) has studied future video coding (FVC) technologies with a potential compression capacity that significantly exceeds that of the high‐efficiency video coding (HEVC) standard. The joint exploration test model (JEM), a common platform for the exploration of FVC technologies in the JVET, employs quadtree plus binary tree block partitioning, which enhances the flexibility of coding unit partitioning. Despite significant improvement in coding efficiency for chrominance achieved by separating luminance and chrominance tree structures in I slices, this approach has intrinsic drawbacks that result in the redundancy of block partitioning data. In this paper, an adaptive tree structure correlating luminance and chrominance of single and dual trees is presented. Our proposed method resulted in an average reduction of −0.24% in the Y Bjontegaard Delta rate relative to the intracoding of JEM 6.0 common test conditions.